Epitelio del conducto deferente de Agouti paca. Observaciones de estructura fina - Orsi, Antonio M. [UNESP]; Simões, Karina; Domeniconi, Raquel F. [UNESP]; da Cruz, Claudinei [UNESP]; Machado, Má R. F. [UNESP]; Filho, Joffre G. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
The surface epithelium of the vas deferens of Agouti paca, a wild and large South American rodent, was basically formed by principal and basal cells being only the principal cells related to endocytosis processes and also secretion taking base on their cytoplasmic ultrastructural features. Principal cell of vas deferens epithelium were characterized mainly by presence of vesicles with several shapes, sizes and internalized content at their apical cytoplasm occurring smaller pits and pale small vesicles seen next to the apical brush border of microvillus. Moreover, coated vesicles, smooth surface vesicles and great vesicles; multivesicular bodies, endosomes and lysosomes were seen. Presence of an apocrine secretory apparatus was also viewed, showing apical cytoplasmic expansions protruding into the vas deferens luminal compartment. The basal flattened cells, without luminal surface contact, occurred next to the basement membrane of the ductus, and did no exhibit special ultrastructural features.
Vas deferens surface epithelium of agouti paca: Fine structural features
Keywords: Fine structure; Histophysiology; South American rodent; Vas deferens epithelium